O papel das experiências de consumo na satisfação de consumidoras da terceira idade: um estudo em salões de beleza - Aragão, Amanda Azevêdo de Castro Frota (2017)
The aging of the population and the lack of personalized products and services for the elderly public aroused the interest in understanding the role of consumer experiences in the satisfaction of the elderly consumers, focusing on the study of beauty salons. Thus, the present work sought to understand the role of consumer experiences in beauty salons in the construction of consumer satisfaction of the elderly, using as technique of data collection and analysis the critical incident technique. Thereby, it was possible to describe consumption experiences and divide them into pre-consumption, purchase / consumption and post-consumption. It was also possible to identify the main elements related to the satisfaction of elderly consumers, such as quality, service, propensity to repurchase and expectation. The relationship observed between consumer experiences and satisfaction showed that in the experience of pre-consumption the presence of quality and expectation elements is present, in the experience of purchase / consumption there is the presence of quality, service and propensity to repurchase and in the post consumer all elements of satisfaction is present. The results contribute to service companies and, especially, to beauty companies. This study made it possible to conclude that satisfaction is directly related to consumer experiences of the elderly customers. KeywordsKeywordsKeywords Keywords